1338. A Pooled Analysis of Patients With Wound Infections in the Phase 3 REVIVE Trials: Randomized, Double-blind Studies to EValuate the Safety and Efficacy of Iclaprim Vs. Vancomycin for trEatment of Acute Bacterial Skin and Skin Structure Infections. (26th November 2018) - Huang, David; Corey, G Ralph; Holland, Thomas L; Lodise, Thomas P; O'Rirodan, William; Wilcox, Mark; File, Thomas M; Dryden, Matthew; Torres, Antoni; Balser, Barbara; Desplats, Eve
Abstract: Background: The objective of this evaluation was to provide an analysis of pooled efficacy data from two parallel Phase 3 trials of iclaprim, a diaminopyrimidine dihydrofolate reducatase inhibitor, compared with vancomycin for the treatment of patients with wound infections including surgical site infections (SSI). Methods: A pooled analysis of patients with wound infections was conducted from two parallel Phase 3, double-blind, randomized (1:1), active-controlled, multinational, multicenter trials (REVIVE-1 and REVIVE-2), which included a total of 602 patients with wound infections. The data were analyzed separately and then pooled to determine the efficacy of iclaprim 80 mg fixed dose compared with vancomycin 15 mg/kg. Both drugs were administered intravenously every 12 hours for 5 to 14 days according to the investigator assessment of clinical response. The primary endpoint of these studies was to determine whether iclaprim was noninferior (NI; 10% margin) to vancomycin in achieving a ≥20% reduction in lesion size (early clinical response [ECR] at 48 to 72 hours after initiation of the study drug (early time point [ETP]), compared with baseline in the intent-to-treat (ITT) population. Results: Iclaprim had similar ECR rates at ETP compared with vancomycin among the subset of patients with wound infections (see table). The median treatment duration for both iclaprim and vancomycin was 7 days (range 5–14 days). Conclusion: In this post-hoc analysis of the REVIVE studies, iclaprim achieved NI to vancomycin in both studies, based on ECR at ETP, in the subgroup of patients with wound infections. These results suggest that iclaprim may be a valuable treatment option for patients with wound infections, including SSI, suspected or confirmed to be due to Gram-positive pathogens. Disclosures: D. Huang, Motif BioSciences: Employee, Salary. G. R. Corey, Motif BioSciences: Board Member, Consulting fee. T. L. Holland, Basilea: Consultant, Consulting fee. Motif Bio: Consultant and Scientific Advisor, Consulting fee. Theravance: Consultant, Speaker honorarium. Genentech: Consultant, Consulting fee. T. P. Lodise Jr., Motif BioSciences: Board Member, Consulting fee. W. O'Rirodan, Motif BioSciences: Board Member, Consulting fee. M. Wilcox, Motif BioSciences: Board Member, Consulting fee. T. M. File Jr., Motif BioSciences: Board Member, Consulting fee. M. Dryden, Motif BioSciences: Board Member, Consulting fee. B. Balser, Motif BioSciences: Consultant, Consulting fee. E. Desplats, Motif BioSciences: Consultant, Consulting fee.